2018
DOI: 10.3389/fimmu.2018.00982
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Genetically Modulate Dendritic Cells to Potentiate Anti-Tumor Responses in Hematologic Malignancies

Abstract: Dendritic cell (DC) vaccination has been investigated as a potential strategy to target hematologic malignancies, while generating sustained immunological responses to control potential future relapse. Nonetheless, few clinical trials have shown robust long-term efficacy. It has been suggested that a combination of surmountable shortcomings, such as selection of utilized DC subsets, DC loading and maturation strategies, as well as tumor-induced immunosuppression may be targeted to maximize anti-tumor responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 124 publications
(187 reference statements)
0
9
0
Order By: Relevance
“…Although FcR-mediated phagocytosis has also been reported to be mechanosensitive 78 , how these receptors are linked to the cytoskeleton is not known. Elucidating the mechanisms of phagocytic mechanosensitivity could enable engineering of dendritic cells or macrophages with improved anti-tumor response 79 or drugbearing particles that evade phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although FcR-mediated phagocytosis has also been reported to be mechanosensitive 78 , how these receptors are linked to the cytoskeleton is not known. Elucidating the mechanisms of phagocytic mechanosensitivity could enable engineering of dendritic cells or macrophages with improved anti-tumor response 79 or drugbearing particles that evade phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical trial on therapeutic cancer vaccine was carried out in 1998 on patients with melanoma [93]. Since the activation of the antigen-presenting ability of DCs is directly related with the induction of the CD8 + T cell response, researchers have focused on the modification of DCs in order to enhance the anti-tumor immune responses in vivo [9496]. Many studies have demonstrated that most malignant tumors, including lung cancers, can produce a variety of factors that suppress anti-tumor immunity.…”
Section: Progress In the Clinical Application Of DC Function Restorationmentioning
confidence: 99%
“…BM-derived DCs (BMDCs) serve as a model for investigating fundamental mechanisms of DC biology, and more broadly, engineered DCs may constitute the critical material for future cell-based vaccines. A traditional method of differentiating BM cells into DCs involves supplementation with GM-CSF (Cornel et al, 2018;Gundry et al, 2016). However, this does not produce the different physiologically relevant subsets found in vivo.…”
Section: Resultsmentioning
confidence: 99%